Differential impact of genetic deletion of TIGIT or PD-1 on melanoma-specific T-lymphocytes - Gwenann Cadiou; Tiffany Beauvais; Lucine Marotte; Sylvia Lambot; Cécile Deleine; Caroline Vignes; Malika Gantier; Melanie Hussong; Samuel Rulli; Anne Jarry; Sylvain Simon; Bernard Malissen; et al. (OncoImmunology)
Immune checkpoint (IC) blockade and adoptive transfer of tumor-specific T-cells (ACT) are two major strategies to treat metastatic melanoma. Their combination can potentiate T-cell activation in the suppressive tumor microenvironment, but the autoimmune adverse effects associated with systemic injection of IC blockers persist with this strategy. ACT of tumor-reactive T-cells defective for IC expression would overcome this issue. For this purpose, PD-1 and TIGIT appear to be relevant candidates, because their co-expression on highly tumor-reactive lymphocytes limits their therapeutic efficacy within the tumor microenvironme,nt. Our study compares the consequences of PDCD1 or TIGIT genetic deletion on anti-tumor properties and T-cell fitness of melanoma-specific T lymphocytes. Transcriptomic analyses revealed down-regulation of cell cycle-related genes in PD-1KO T-cells, consistent with biological observations, whereas proliferative pathways were preserved in TIGITKO T-cells. Functional analyses showed that PD-1KO and TIGITKO T-cells displayed superior antitumor reactivity than their wild-type counterpart in vitro and in a preclinical melanoma model using immunodeficient mice. Interestingly, it appears that TIGITKO T-cells were more effective at inhibiting tumor cell proliferation in vivo, and persist longer within tumors than PD-1KO T-cells, consistent with the absence of impact of TIGIT deletion on T-cell fitness. Taken together, these results suggest that TIGIT deletion, over PD-1 deletion, in melanoma-specific T-cells is a compelling option for future immunotherapeutic strategies.